MACRO VBA-BASED MAIL SERVICE ADMINISTRATION INFORMATION SYSTEM IN VILLAGES AND SATISFACTION ANALYSIS USING NAÃVE BAYES CLASIFICATION - Dudih Gustian; A. Oktian Permana; Sihabudin; Lucas Crammer (Nusa Putra University, 2023)
Based on the Law of the Republic of Indonesia Number 25 of 2009 concerning Services, public services must achieve good and clean governance, have less time discipline and tend to slow down the process, as well as a lack of professionalism from employees who are not responsible for their work. In addition to providing benefits and information to the village government, administrative services for research letters also affect quality and performance. The stages that will be carried out in this study include observation, interviews, and literature study from previous research. The Naïve Bayes classification method is used in this study, where the basic calculation is based on the probability of each attribute. If an attribute with a certain class has a value of zero, then the probability of that class will also be zero, and this will affect the final result of the Naïve Bayes calculation. Questionnaire result data is divided into 60% training data, 40% testing data, and 10% validation data. The evaluation results show an accuracy rate of 98.6% for training data, 100% for testing data, and 97.2% for validation data. The comparison shows that there is only a change of 2% after using the mail service administration information system